Brexit as a keyword in British political discourse - Fomenko , Olena (Current issues of Ukrainian linguistics: theory and practice, 2023)
This case study examines the neologism Brexit, defined in OED as "the (proposed) withdrawal of the United Kingdom from the European Union and political processes associated with it." Coined in May 2012, this word quickly gained media currency in the United Kingdom and abroad. The political coinage has become an internationalism, i.e., it has achieved global recognition and entered other languages in its original meaning and form. After an unprecedented surge in use (by astronomical 3 400%), Brexit was declared the 2016 word of the year by Collins Dictionary and gained entry to the Oxford English Dictionary. This study explores the word's characteristics and use in the media. The data were collected from British internet magazines and newspapers and the NOW corpus (News on the Web) for the time period from May 2012 to January 2023. The study argues that the word Brexit has the following features of a keyword: social significance, high frequency, wide use in various contexts, occurrence in strong media positions, metaphorical creativity, and neological productivity. Brexit appears on magazine covers, newspaper front pages, and in headlines. Reflecting heated debates on the British exit from the EU, the word has acquired new and controversial meanings and become a rich source of word formation, thus giving rise to numerous neologisms collectively referred to as Brexit glossary or Brexicon. This glossary of Brexit terms includes "old" English words and expressions that have acquired new meanings and political terms used in everyday discussions about Brexit. The most significant contribution of the word Brexit to present-day English is the new productive suffix -exit that, transcending the boundaries of political discourse, has come into use in various other domains.
Keywords: neologism, keyword, Brexit, political discourse, British media.